Palladium-Catalyzed Approach to Malasseziazole A and First Total Synthesis of Malasseziazole C - Kober, Ute; Knölker, Hans-Joachim (Synlett, 2015)
We describe a convergent route to 5,11-dihydroindolo[3,2-b]carbazoles using a twofold oxidative cyclization as key step. The method has been applied to the synthesis of a precursor for malasseziazole A and to the first total synthesis of malasseziazole C.
Keywords: alkaloids; catalysis; cyclization; indolocarbazoles; natural products; palladium